2018
DOI: 10.1136/bjsports-2018-099821
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prenatal exercise on maternal harms, labour and delivery outcomes: a systematic review and meta-analysis

Abstract: ObjectiveTo perform a systematic review of the relationships between prenatal exercise and maternal harms including labour/delivery outcomes.DesignSystematic review with random effects meta-analysis and meta-regression.DatasourcesOnline databases were searched up to 6 January 2017.Study eligibility criteriaStudies of all designs were included (except case studies) if they were published in English, Spanish or French and contained information on the population (pregnant women without contraindication to exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 106 publications
4
80
0
2
Order By: Relevance
“…26,27 A recent systematic review that evaluated potential maternal and fetal harms as a result of exercise during pregnancy reported that exercise did not have an association with preterm rupture of membranes, caesarean births, induction of labor, length of labor, vaginal tears, or musculoskeletal trauma. 28 In fact, exercise has actually shown protective effects for both maternal and fetal health, including improvement in cardiovascular fitness that can assist with labor and recovery. 29 As women who are pregnant continue to report fear for safety as a concern and deterrent for participating in exercise, this may indicate a lack of knowledge translation for the known benefits and lack of harms associated with prenatal exercise.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 A recent systematic review that evaluated potential maternal and fetal harms as a result of exercise during pregnancy reported that exercise did not have an association with preterm rupture of membranes, caesarean births, induction of labor, length of labor, vaginal tears, or musculoskeletal trauma. 28 In fact, exercise has actually shown protective effects for both maternal and fetal health, including improvement in cardiovascular fitness that can assist with labor and recovery. 29 As women who are pregnant continue to report fear for safety as a concern and deterrent for participating in exercise, this may indicate a lack of knowledge translation for the known benefits and lack of harms associated with prenatal exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by the 2016 Evidence summary of the International Olympic Committee expert group meeting on exercise and pregnancy in recreational and elite athletes concluded that exercise did not increase the risk of induction, epidural, episiotomy or perineal tears, and forceps or vacuum delivery, but appeared to be associated with a shorter first stage of labor and lower risk of cesarean delivery [85]. Similarly, a recent systematic review and meta-analysis concluded that based on moderate quality evidence from 20 exercise-only RCTs conducted antenatally (n = 3819), the odds of instrumental delivery in women who exercised was lower than those who did not; there were no differences between groups in any other labor/delivery variables studied [86]. However, the conclusions were based on few studies (mostly retrospective and prospective observational studies) and the studies had low-to-moderate quality [85,86].…”
Section: Easier Labor and Birthmentioning
confidence: 99%
“…Those women are counselled to seek physiotherapy advice and avoid abdominal strengthening exercises (eg, abdominal curls) as this may worsen the condition,31 increasing the likelihood of requiring postnatal repair. However, continuing aerobic exercise such as walking is associated with decreased odds of developing diastasis recti 4. While there has been less research on resistance exercises as compared with aerobic exercises in pregnancy, available evidence regarding resistance exercise in pregnancy has not identified adverse impacts on the mother, the fetus or the neonate.…”
Section: Considerations For Implementationmentioning
confidence: 99%